Comparision Effectivness of Extracts of Thyme, Yarrow, Henna and Garlic on Cutaneous Leishmaniasis Caused by L. major in Animal Model (Balb/c) - SH Hejazi; L Shirani - Bidabadi; A Zolfaghari – Baghbaderani; S Saberi; MA Nilforoushzadeh; SH Moradi; M Mahmoudi; SH Khosravi; A Ataei (Journal of Medicinal Plants, 2009)
Background: Leishmaniasis is not as severe as other diseases, often lesions are selfhealing. For various reason as long lasting duration of lesions and treatment, disfiguring scar reminding, secondary infection in lesions, have comfortable treatment method and accessible with less cost, it is necessary various method of treatment with less side effect. The results of previous studies showed that Indoleanalogues, Terpens, Iridoids, Quinones and Alkaloid hemisynthetic derivatives have promising antileishmanial potential. These derivatives were found in Thyme, Henna Yarrow and Garlic. Objective: Access to formulation drug without harmful chemical material and without side effect. Methods: After Inoculation of parasite in base tail of mice, during of three weeks caused lesions in inoculation place, then animal divided to 9 groups. In this study we used 4 alchoholic extract solution 2 times a day. we checked lesions weekly for six week and meseaured size of lesion in the base of tail with kulis – vernieh. Data of study analyzed with Anova, Paired t test and schefeh. Results: We observed significant difference between mean of lesion in before and after treatment in control, Yarrow (Bomadaran) and Thyme (Avishan) groups (p<0.05). Paired t test showed that there were not significant difference between mean of lesion in after treatment between groups of treatment and glucantime groups (p>0.05). Conclusion: Alchoholic extract to Avishan and Boomadaran have good effect on lesions treatment, we suggest that the study could be repeated with Thyme (Avishan) and Yarrow (Bomadaran) extract in gel or cream base in first stage of lesions appearance.